2007
DOI: 10.1158/0008-5472.can-06-4793
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Activity of CCAAT/Enhancer Binding Protein α Is Epigenetically Down-regulated in Head and Neck Squamous Cell Carcinoma

Abstract: Tumor suppressor CCAAT enhancer binding protein a (C/EBPa) is a transcription factor involved in cell cycle control and cellular differentiation. In a recent study, microarray expression profiling on head and neck squamous cell carcinoma (HNSCC) samples identified significant C/EBPa down-regulation, correlating with poor prognosis. However, the mechanisms of C/EBPa down-regulation remained elusive. C/EBPa has been previously found to provide an antiproliferative role in lung cancer, and our laboratory showed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 43 publications
(55 reference statements)
3
73
0
Order By: Relevance
“…Aberrant promoter hypermethylation may serve as an alternative mechanism to deletion and mutation in abrogating the function of tumour suppressor genes. While it is clear that DNA hypermethylation of the upstream promoter region of C/EBPA gene is responsible for very low C/EBPA expression in human endometrial and lung cancer [12,13], there appears to be a controversial issue how frequent the promoter hypermethylation of C/EBPA gene presents in CN-AML patients. It was reported by Chim et al in 2002 that hypermethylation of C/EBPA gene promoter was very infrequent in AML patients (only two patients, both with M2 morphology, had methylated C/EBPA in 70 AML patients studied) [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant promoter hypermethylation may serve as an alternative mechanism to deletion and mutation in abrogating the function of tumour suppressor genes. While it is clear that DNA hypermethylation of the upstream promoter region of C/EBPA gene is responsible for very low C/EBPA expression in human endometrial and lung cancer [12,13], there appears to be a controversial issue how frequent the promoter hypermethylation of C/EBPA gene presents in CN-AML patients. It was reported by Chim et al in 2002 that hypermethylation of C/EBPA gene promoter was very infrequent in AML patients (only two patients, both with M2 morphology, had methylated C/EBPA in 70 AML patients studied) [14].…”
Section: Resultsmentioning
confidence: 99%
“…Inactivation of gene expression by abnormal hypermethylation of CpG islands in promoter region in many tumor suppressor genes has been clearly recognized. It has been reported that DNA hypermethylation of the upstream C/EBPA promoter region is responsible for very low C/EBPA expression in human endometrial and lung cancer [12,13]; However, it is controversial whether there has frequent DNA hypermethylation of the upstream C/EBPA promoter region in AML. Some previ-ous studies showed C/EBPA promoter hypermethylation was relatively infrequent in AML [14,15]; while more recent investigations demonstrated that aberrant methylation of the C/EBPA gene promoter region often occurred in a subset of AML patients particularly in specific subtype of AML cases with aberrant expression of T-cell associated antigens [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…16 Tada et al 15 demonstrated that the interaction of MBD2 and MeCP2 methyl-CpG binding proteins with the upstream promoter regulatory region spanning -1413 to -887 bp from TSS was associated with the decrease of CEBPA expression in lung cancer cell lines. In the -1256 to -831 region there are binding sites for the transcriptional factors USF-1/-2 and Sp1, thus suggesting that methylation decreases the cis-activity of these factors, leading to lower CEBPA expression.…”
Section: Dna Methylation Status Analysis Of the Cpg Islands In The Comentioning
confidence: 99%
“…Mutations in CEBPA occur exclusively in haematological diseases and result in perturbed C/EBPα protein expression and function. C/EBPα promoter methylation perturbs C/EBPα expression in AML(1), CML (2), and head and neck squamous cell carcinoma (3). In AML, oncogene-mediated dysregulation of C/EBPα mRNA expression and/or protein activity occurs in CEBPA is an intronless gene with N-terminal transcriptional activation domains and a C-terminal basic region leucine zipper (LZ) domain.…”
Section: Introductionmentioning
confidence: 99%